Human Fetal Pigmented Ciliary Epithelium Stem Cells have Regenerative Capacity in the Murine Retinal Degeneration Model of Laser Injury - Bammidi, Sridhar; Modgil, Shweta; Kalra, Jaswinder; Anand, Akshay (Current Neurovascular Research, 2019)
Background: Retinal degeneration and related eye disorders have limited treatment interventions. Since stem cell therapy has shown promising results, ciliary epithelium (CE) derived stem cells could be a better choice given the fact that cells from eye niche can better integrate with the degenerating retina, rewiring the synaptic damage. Objective: To test the effect of human fetal pigmented ciliary epithelium-derived neurospheres in the mouse model of laser-induced retinal degeneration. Methods: C57 male mice were subjected to retinal injury by Laser photocoagulation. Human fetal pigmented ciliary epithelium was obtained from post-aborted human eyeballs and cultured with epidermal growth factor (rhEGF) and fibroblast growth factor (rhFGF). The six day neurospheres were isolated, dissociated and transplanted into the subretinal space of the laser injured mice at the closest proximity to Laser shots. Mice were analyzed for functional vision through electroretinogram (ERG) and sacrificed at 1 week and 12 week time points. Retinal, Neurotropic, Apoptotic and proliferation markers were analysed using real-time polymerase chain reaction (PCR). Results: The CE neurospheres showed an increase in the expression of candidate genes analyzed in the study at 1 week time point, which sustained for longer time point of 12 weeks. Conclusion: We showed the efficacy of human CE cells in the regeneration of retinal degeneration in murine model for the first time. CE cells need to be explored comprehensively both in disease and degeneration.
Keywords: Ciliary epithelium